TAS-102 (trifluridine/tipiracil) plus bevacizumab versus TAS-102 alone as salvage treatment options for metastatic colorectal cancer in routine clinical practice - Shin, Ji Eun; Lim, Sung Hee; Lee, Jeeyun; Lim, Ho Yeong; Park, Young Suk; Kim, Seung Tae (Frontiers in Oncology, 2024)
IntroductionBoth regimens of TAS-102 (trifluridine/tipiracil) with and without bevacizumab are considered standard options for salvage treatment in patients with refractory metastatic colorectal cancer.Materials and methodsThis analysis included patients with metastatic colorectal cancer who received either TAS-102 plus bevacizumab or TAS-102 alone between July 2022 and November 2023 at Samsung Medical Center. We evaluated the objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and safety profile of both regimens.ResultsIn total, 139 patients were included in this analysis. Median age was 60.8 years, and median number of previous lines of therapy was four (range: 2.45–6.55). More than half of the subjects (56.8%) had RAS mutations and 92.9% received previous anti-VEGF therapy. 83 (59.7%) patients received the combination of TAS-102 and bevacizumab and 56 (40.3%) received TAS-102 alone. The number of patients with prior regorafenib treatment was 14 in the TAS-102 with bevacizumab group and 5 in the TAS-102 alone group. The disease control rate was 51.8% in the combination group and 32.1% in the TAS-102 alone group. The median PFS was 3.3 months (95% CI, 2.7–6.6) in the combination group and 2.5 months (95% CI, 2.0–3.8) in the TAS-102 alone group (HR, 0.56; 95% CI, 0.38–0.82; p=0.003). The median OS in these two groups was 10.8 months (95% CI, 8.4–NA) and 6.0 months (95% CI, 4.8–9.8), respectively (HR, 0.62; 95% CI, 0.40–0.97, p=0.033). In the exploratory analysis of TAS-102 + Bev group, patients with the KRAS G12 mutation had inferior OS compared to those without the mutation (HR, 2.01, 95% CI, 1.04–3.90, p=0.035). Commonly observed adverse events were hematologic-related, including neutropenia, anemia, and thrombocytopenia, as well as nausea. While any grade neutropenia was observed at similar frequencies in the two groups (57.8% and 57.1%), grade 3 or higher neutropenia was more frequent in the combination group than the TAS-102 alone group (31.3% vs. 17.9%). Among patients who received subsequent anticancer therapy after treatment failure, 74.1% received regorafenib.ConclusionsThe combination of TAS-102 and bevacizumab resulted in a better survival outcome than TAS-102 monotherapy, consistent with previous studies. This analysis supports the use of the combination of TAS-102 and bevacizumab as the best therapeutic option for patients with refractory metastatic colorectal cancer in clinical practice.